Augmented Reality in Science Education: A Systematic Literature Review of Research Trends in Indonesia (2020–2025) - Sudarto Sudarto; Bambang Subali (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2025)
The rapid evolution of digital technology necessitates fundamental transformations in educational practice, most notably through the systematic integration of Augmented Reality (AR) as an innovative pedagogical tool. This study analyzes AR research trends in science education within the Indonesian context over the period 2020–2025. Employing a bibliometric approach guided by the PRISMA protocol, a final corpus of 471 relevant articles was systematically synthesized from an initial pool of 985 records retrieved from Publish or Perish and Mendeley databases. Bibliometric data were visualized using VOSviewer through network, overlay, and density analyses to map the intellectual structure and thematic evolution of the field. The findings reveal a consistent upward trajectory in annual AR publication output, peaking in 2024. AR implementation is most prevalent at the senior high school level, theoretically consistent with Piaget's formal operational stage, wherein learners require visual scaffolding to engage with abstract scientific concepts. A significant methodological gap is identified: existing research is predominantly characterized by quantitative efficacy testing, with a conspicuous scarcity of qualitative investigations into pedagogical barriers and shifts in student learning behavior. This study contributes a distinctive perspective through thematic mapping within the Indonesian educational context, identifying underexplored opportunities in collaborative AR-based learning and long-term cognitive retention. Two principal recommendations are proposed: teachers are encouraged to integrate AR into inquiry-based learning worksheets as dynamic pedagogical scaffolds rather than static visual aids, and policymakers are urged to standardize digital infrastructure and develop validated AR content repositories to ensure equitable technology adoption across all educational levels in Indonesia.